2011
DOI: 10.1111/j.1365-3040.2011.02439.x
|View full text |Cite
|
Sign up to set email alerts
|

Vulnerability curves by centrifugation: is there an open vessel artefact, and are ‘r’ shaped curves necessarily invalid?

Abstract: Vulnerability curves using the 'Cavitron' centrifuge rotor yield anomalous results when vessels extend from the end of the stem segment to the centre ('open-to-centre' vessels). Curves showing a decline in conductivity at modest xylem pressures ('r' shaped) have been attributed to this artefact. We determined whether the original centrifugal method with its different rotor is influenced by open-to-centre vessels. Increasing the proportion of open-to-centre vessels by shortening stems had no substantial effect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
131
1
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(144 citation statements)
references
References 24 publications
10
131
1
2
Order By: Relevance
“…The species we used were all shrubs with relatively short vessels (Hacke et al 2009). More importantly, we have not found vessel length artifacts with the centrifuge technique used in the present study (Sperry et al 2012;Jacobsen and Pratt 2012;Tobin et al in press). …”
Section: Xylem Vulnerability To Cavitationsupporting
confidence: 48%
“…The species we used were all shrubs with relatively short vessels (Hacke et al 2009). More importantly, we have not found vessel length artifacts with the centrifuge technique used in the present study (Sperry et al 2012;Jacobsen and Pratt 2012;Tobin et al in press). …”
Section: Xylem Vulnerability To Cavitationsupporting
confidence: 48%
“…The most likely cause of this artifact is that microbubbles, which move into the sample either prior to, or during, the spinning phase lead to embolism formation when they reach the center of the sample where centrifugal forces are highest (Wang et al, 2014). This open-vessel artifact has been the subject of intense debate, with some researchers suggesting that the artifact only affects the Cavitron version of the centrifuge technique and not the static centrifuge method Jacobsen and Pratt, 2012;Sperry et al, 2012;Tobin et al, 2013;Hacke et al, 2015). Data from this study demonstrate that static and spin centrifuge techniques produced similarly biased results for Q. robur.…”
Section: Speciesmentioning
confidence: 99%
“…This artifact occurs when samples placed into centrifuge rotors or air injection collars have a large proportion of vessels that are cut open at both ends of the segment. A number of studies have disputed this open-vessel hypothesis and suggested that some versions of the centrifuge and air injection techniques provide reliable estimates of cavitation resistance (Jacobsen and Pratt, 2012;Sperry et al, 2012;Tobin et al, 2013). Because there will always be uncertainties associated with indirect measurements, noninvasive imaging using intact plants provides the best option for resolving these methodological issues.…”
mentioning
confidence: 99%
“…S1). Controversy has recently arisen regarding measurements of stem and root hydraulic traits (24), in particular about whether nonsigmoidal vulnerability relationships (i.e., of K vs. Ψ) are caused by methodological artifacts that overestimate vulnerability. We tested the correlations across species by using all available data (SI Appendix, SI Methods), but confirmed our conclusions for the smaller dataset derived from sigmoidal relationships (n = 285) and present these results in the main text (Dataset S1).…”
mentioning
confidence: 99%